Dirâsah Taqâbuliyyah Baina Al-Lughah Al-‘Arabiyyah Wa Al Lughah Al-Indûnîsiyyah ‘Alâ Mustawâ Ismi At-Tafdhil Wa Al Istifâdah Minhâ Fî Ta‘lîm Al-Lughah Al-‘Arabiyyah Li Al Mubtadi’în Al-Indûnisiyyîn - Ilyas Habibulloh; Said Hassan Nassila (Mauriduna: Journal of Islamic Studies, 2020)
هدفت هذه الدراسة إلى دراسة اسم التفضيل في اللغة العربية ونظيره في اللغة الإندونيسية لاكتشاف أوجه التشابه والاختلاف بينهما من الناحية الصرفية والنحوية والدلالية أولا، ثم إعداد وحدة دراسية لتعليم اللغة العربية على مستوى اسم التفضيل للمبتدئين الإندونيسيين بناء على نتائج هذه الدراسة ثانيا. واستخدمت المنهج الوصفي التحليلي للوقوف على خصائص اسم التفضيل في اللغتين العربية والإندونيسية، ومنهج التحليل التقابلي لمقارنة نظام اسم التفضيل بين اللغتين العربية والإندونيسية واستنباط التشابه والاختلاف بينهما. وقد توصلت هذه الدراسة إلى نتيجتين؛ أولهما: وجود تشابه واختلاف بين اللغتين العربية والإندونيسية من الناحية الصرفية والنحوية والدلالية، وثانيهما أنه يمكن الاستفادة من نتائج هذه الدراسة في إعداد وحدة دراسية لتعليم اللغة العربية على مستوى اسم التفضيل للمبتدئين الإندونيسيين. This study aimed to knowing degree of comparison between Arabic and Indonesian to find out the similarities and differences in terms of morphology, syntax, and semantic to preparation of the lesson to teach Arabic language at the level of the comparison of adjectives for the Indonesian beginners based on the results of this contrastive study. This study used descriptive analytical methodology to identify the characteristics of degree of comparison in Arabic and Indonesian, and used method of comparative analysis to compare the Arabic and Indonesian at the level of degree of comparison and to deriving of their similarities and differences. The results of this study are: the first is there are similarities and differences of degree of comparison in Arabic and Indonesian in terms of morphology, syntax, and semantic, and the second is the results of this study can be used in preparing Arabic language lesson at the level of degree of comparison for the indonesian beginners.